Externalization and Securitization as Policy Responses to African Migration to the European Union (African Human Mobility Review, 2021)
This paper examines how African migration to the European Union (EU) has becomeexternalized and securitized and the implications this has for migration managementfor both the EU and Africa. To accomplish this, the paper employed a qualitative researchapproach which reviewed current literature on the topic under study. It foundthat the externalization and securitization of African migration to the EU have failedto prioritize and address the different socio-economic and political conditions that aredriving irregular migration. Additionally, externalization and securitization as policyresponses do not stop irregular African migration; rather, they prolong the misery ofmigrants who are at the mercy of smugglers who prey on their desperation. The paperconcludes that migration management between the EU and Africa needs to be anchoredon policies that address the core ‘push’ factors driving irregular migration fromAfrica, rather than policies which do not stop migration (even though they have slowedit down) but rather indirectly empower smugglers and leave considerable room for theabuse of migrants.